Trends in antibiotic susceptibility patterns and epidemiology of MRSA isolates from several hospitals in Riyadh, Saudi Arabia - Abuelkheir Manal M; Baddour Manal M; Fatani Amal J (BMC, 2006)
Abstract Background Methicillin-resistant Staphylococcus aureus (MRSA), is associated with high morbidity and mortality rates with rapid development of resistance. Methods A total of 512 MRSA isolates were procured from 6 major hospitals in Riyadh, Saudi Arabia and antibiotic susceptibilities and MICs were documented against several antibiotics and vancomycin. SPSS version 10 was used for statistical analysis. Results The prevalence of MRSA in the study hospitals ranged from 12% to 49.4%. Mean patient age was 44 years with males constituting 64.4% and females 35.6%. Approximately 41.5% of the isolates came from patients in the extreme age groups. MIC for vancomycin was in the susceptible range for all isolates ranging from 0.25 to 3 ug/ml. The overall susceptibility of MRSA to the various antibiotics tested was: fusidic acid 4.3%, sulfamethoxazole/trimethoprim 33.8%, gentamicin 39.6%, mupirocin 77.0%, gatifloxacin 78.9%, chloramphenicl 80.7%, linezolid 95.1%, quinupristin/dalfopristin 100%. Some differences were noted in the resistance of isolates among the participating hospitals reflecting antibiotic usage. On the whole, inpatient isolates (accounting for 77.5% of the isolates) were more resistant than outpatient isolates (22.5%) except for linezolid. Quinupristin-dalfopristin and linezolid are the most effective antibiotics tested against inpatient isolates while quinupristin-dalfopristin and gatifloxacin seem to be the most effective against outpatient isolates. Approximately one forth of the isolates are no longer susceptible to mupirocin used for eradication of the carrier state reflecting resistance developing after widespread use. Trends over time show a tendency towards decreased susceptibility to gatifloxacin and linezolid with increasing susceptibility to gentamicin and sulfamethoxazole/trimethoprim. Conclusion Quinupristin/dalfopristin and linezolid are two valuable additions to our antimicrobial armamentarium, but resistance has already been described. To preserve their value, their use should be limited to those rare cases where they are clearly needed. Fusidic acid, the local antibiotic, gentamicin and trimethoprim/sulfamethoxazole should not be relied upon for treatment of MRSA infections, at least empirically as the percentage of susceptible isolates is very low.